Effects of Vacuum and Shaking on Flavor Substances of Longnan White Tea - LI Yonghua, WU Peng, XU Jianhan, YUAN Xuexia, ZHANG Lin, GAO Rui, Bi Jingxiu, JIANG Yuying, ZHAO Tong, HAO Haining, WANG Huijun, LIU Pingxiang, WANG Yutao (Shipin Kexue)
In this study, ultra-high performance liquid chromatography-triple quadrupole-tandem mass spectrometry (UPLC-TQ-MS/MS) and full 2D gas chromatography-time of flight mass spectrometry (GC × GC-TOFMS) were used to analyze the phenolic compounds, amino acids, purine alkaloids, and volatile constituents in Longnan white tea, and multivariate statistical analyses such as principal component analysis (PCA), were used to systematically evaluate the effects of vacuum combined with shaking on the biochemical and volatile constituents of Longnan white tea. The results showed that the combined treatment significantly increased the content of γ-aminobutyric acid in white tea to 1.54 mg/g, but decreased the contents of phenolics, catechins and caffeine differently, the large decrease being in epigallocatechin gallate (EGCG). Compared with the control group, vacuum treatment alone and followed by shaking decreased the EGCG content by 54.95% and 75.40%, respectively. Sensory evaluation showed that the three tea samples prepared by different processing methods each had their own aroma and taste characteristics. Compared with the control and vacuum treatment groups, white tea prepared by vacuum plus shaking showed a stronger and purer aroma with sweet and fruity notes as well as a slight floral note, and tasted sweet and mellow. Further analysis showed that vacuum treatment increased the number of volatile components, and compared with single vacuum treatment, the combined treatment increased the content of alcohols such as nerolidol, and decreased the content of unpleasant odors such as difurfuryldisulfide. Combining the results of odor activity value (OAV) and aroma character impact (ACI), we found that (E)-3,7-dimethyl-2,6-octadienal, nerolidol, and isoamyl aldehyde were the key aroma components in white tea prepared by sequential vacuum and shaking treatment, contributing to its obvious fruity aroma. Furthermore, this tea had a weaker irritating odor and tasted softer compared with that obtained from single vacuum treatment. This study provides technical support for the development of γ-aminobutyric acid-rich white tea with high aroma quality, which will promote the high-value development and utilization of Longnan white tea.